Inter-relationship between altered thoracic- kyphosis angle and core stability and its effect on quality of life among female subjects with hyper-kyphosis - Dalal, Aashwi Asheshkumar; Modi, Neha Abhaykumar (International Journal of Research in Medical Sciences, 2023)
Background: The hyper-kyphotic posture may result in altered alignment of the shoulder and pelvic girdle which may develop compensatory changes in the spinal segments above and below. Thus, affecting the components which maintain the core stability. In this study two components namely strength and endurance were evaluated. The main objective was to determine if there was any correlation between the altered thoracic kyphosis and the core stability as well as to study the effect of hyper-kyphosis on quality of life in female subjects. Methods: The study included 84 female subjects from various areas of Surat aged between 20-60 years with thoracic-kyphosis angle more than 50º and were able to read and write Gujarati language. The Thoracic-kyphosis angle was measured using inclinometer and to assess the core stability (1) Static Endurance tests (2) Dynamic Endurance test and (3) Trunk MMT for strength testing was used. The quality of life was assessed using WHOQOL-BREF Gujarati version. Results: Statistically, moderate positive correlation was obtained between age and thoracic-kyphosis angle. There was strong positive correlation between thoracic-kyphosis angle and flexion: extension, thoracic-kyphosis angle and right-side bridge: left-side bridge, thoracic-kyphosis angle and right- side bridge: extension and thoracic-kyphosis angle and left-side bridge: extension. Out of four domains of WHOQOL-BREF the first two domains showed moderate negative correlation. Conclusions: The core stability was hampered more in subjects with more thoracic-kyphosis angle. While only the physical and psychological component of quality of life was affected by the altered thoracic-kyphosis angle.